Parental Social Support and Intellectual Intelligence of Muhammadiyah Elementary Students: Dukungan Sosial Orang Tua dan Kecerdasan Intelektual Siswa Sekolah Dasar Muhammadiyah - Jati , Elvira Hazmi Mutiara; Ansyah, Eko Hardi (Journal of Islamic and Muhammadiyah Studies, 2025)
Background: Children’s intellectual intelligence plays a crucial role in determining learning success. Specific Background: Parental social support is one factor assumed to contribute to children’s cognitive development. Gap: Research investigating the relationship between parental social support and intellectual intelligence in Muhammadiyah Elementary Schools in Gresik remains limited. Aim: This study aims to examine whether parental social support is related to students’ intellectual intelligence. Method: This quantitative study employed a correlational design with 121 students from grades 3 and 5 as participants. Data were collected using a parental social support scale and WISC intelligence test and analyzed using Pearson’s correlation. Results: Findings revealed no significant relationship between parental social support and students’ intellectual intelligence. Novelty: This study provides evidence from a specific school context showing the independence of intellectual intelligence from parental social support levels. Implications: Future research should explore other environmental and psychological factors affecting intellectual development. Highlights : Challenges in descriptive writing Role of teacher support Learning strategies for improvement Keywords: Parental Social Support, Intellectual Intelligence, Elementary Education, WISC, Quantitative Study